2017
DOI: 10.1111/joor.12586
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term changes in chewing efficiency and subjective evaluation in normal dentate subjects after insertion of oral appliances with an occlusal flat table

Abstract: Oral appliances with an occlusal flat table are used as treatment dentures. However, the short-term effect of insertion of such oral appliances on chewing has not been reported. This study aimed to determine whether experimental and continuous insertion of oral appliances with an occlusal flat table has an effect on chewing efficiency and Oral Health Impact Profile (OHIP) in healthy participants. Ten participants each in the oral-appliance and control (no oral-appliance insertion) groups attended six data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It cannot be ruled out that a biological adaptation process might occur if this bite-raising method was used long term. A recent study 25 demonstrated a decrease in chewing efficiency and worse Oral Health Impact Profile (OHIP) questionnaire scores immediately after inserting oral appliances with an occlusal flat table in healthy subjects; however, the OHIP scores of all subdomains, except that of psychological discomfort, improved within 5 days after insertion. The FIA scores after bite-raising in the current study might have improved similarly if longer observation periods were used.…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be ruled out that a biological adaptation process might occur if this bite-raising method was used long term. A recent study 25 demonstrated a decrease in chewing efficiency and worse Oral Health Impact Profile (OHIP) questionnaire scores immediately after inserting oral appliances with an occlusal flat table in healthy subjects; however, the OHIP scores of all subdomains, except that of psychological discomfort, improved within 5 days after insertion. The FIA scores after bite-raising in the current study might have improved similarly if longer observation periods were used.…”
Section: Discussionmentioning
confidence: 99%